Analisis Bentuk Gangguan Berbahasa Disleksia pada Usia Lima Belas Tahun beserta Preventifnya dalam Pembelajaran Membaca - Evi Apriyani; Hendra Setiawan; Uah Maspuroh (Jurnal Ilmiah Wahana Pendidikan, 2022)
This research is based on differences in children's abilities in undergoing their education. At the age of adolescence, essentially children have mastered the concept of reading correctly, in addition to the age factor that has reached the maturity level, adults at the age of teenagers have also experienced a phase of basic reading learning which is at the elementary school level. However, this does not apply to children with dyslexic language disorders. Dyslexia results in children not recognizing, understanding words or sounds in their entirety so that they require appropriate treatment in the form of preventive reading learning materials that are tailored to the needs of dyslexic children. Dyslexia language disorders have different characteristics in each individual. Based on this, it is necessary to conduct research on the form of dyslexia language disorders at the age of fifteen years, so that it is known that preventive reading learning methods are suitable for use. This research method is descriptive qualitative. The data collection technique used a conversational engagement listening technique, recording technique, note-taking technique, documentation. Based on the results of the study showed that the subject was wrong in distinguishing letters both in terms of shape and sound.